Our iceberg is melting : changing and succeeding under any conditions - Kotter, John P., 1947-; Rathgeber, Holger (New York : St. Martin's Press, 2006)
In this business management fable, one penguin notices something problem that could become a big problem for the whole colony, but the other penguins don't want to listen, so he must convince and enlist the help of others to get something done.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Organizational change; Organizational effectiveness; Penguins -- Fiction